SRF programs towards High-Q/High-G cavities in IJCLab - Miyazaki Akira; Fouaidy Mohammed; Gandolfo Nicolas; Longuevergne David; Olry Guillaume; Vannson Mael; Vogt Lê My; Baudrier Matthieu; Cenni Enrico; Eozénou Fabien; Jullien Grégoire; Maurice Luc (EPJ Web of Conferences)
IJCLab has been leading the development and deployment of low-β Superconducting Radio Frequency (SRF) cavities for proton and heavy ion accelerators. We are launching an electron accelerator project for sustainable Energy Recovery Linac (iSAS/PERLE) with state-of-the-art SRF cavities at 800MHz. Our proposal includes advanced heat treatment of such cavities to reach an excellent quality factor of 3 × 1010 at 22 MV/m. In this paper, we overview the status of this activity.